IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH TERHADAP KINERJA GURU IPS TERPADU PADA SMP DI KOTA PALU - Adam, Karima B. (Katalogis, 2016)
The research problem of this study is: (1) How is the implementation of management based school of SMP at Palu?, and (2) How is the implementation of school based management to improve the performance of the SMP social study’s teachers in Palu ?. Moreover, this research aims at: (1) describing the implementation of school based management in relation to the performance of the social study’s teacher. This was a descriptive research with a qualitative approach. The data were collected throught In-depth interview. The results of the interview show that, according to the teachers, the implementation of management based school (MBS) at MTs. Negeri Palu Selatan, SMP Al-Azhar Palu and SMP Negeri Model Terpadu Madani Palu was good as the form of decentralization of education management to the school autonomously. Therefore, the schools have autonomy in determining educational management policies according to the needs, circumstances and the ability of the school. Education management autonomously and independently covers all aspects of supporting education in schools, including: curriculum management, student management, infrastructure management, financial management, public relations management and management of the school with special services. The success of education and teaching process in schools that involve all the components of human resources can be realized in accordance with the national education goals.